2019
DOI: 10.1101/839373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying genetic heterogeneity between continental populations for human height and body mass index

Abstract: Genome-wide association studies (GWAS) in samples of European ancestry have identified thousands of genetic variants associated with complex traits in humans. However, it remains largely unclear whether these associations can be used in non-European populations. Here, we seek to quantify the proportion of genetic variation for a complex trait shared between continental populations. We estimated the between-population correlation of genetic effects at all SNPs ( " ) or genome-wide significant SNPs ( "($%&) ) fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…On the other hand, several studies have shown that heterogeneity in genetic architectures limits transferability of polygenic risk scores (PRSs) across populations; 5,[41][42][43][44][45][46][47][48] critically, if applied in a clinical setting, existing PRSs may exacerbate health disparities among ethnic groups. 49 The population specificity of existing PRSs as well as estimates of transethnic genetic correlations less than one reported in the literature 30,[50][51][52][53] indicate that (1) LD tagging and allele frequencies of shared causal variants vary across populations, (2) that a sizeable number of causal variants are population specific, and/or (3) that causal effect sizes vary across populations due to, for example, different gene-environment interactions. In a region with population-specific LD, a single genetic variant that is significantly associated with a trait in two populations may actually be tagging distinct population-specific causal variants (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have shown that heterogeneity in genetic architectures limits transferability of polygenic risk scores (PRSs) across populations; 5,[41][42][43][44][45][46][47][48] critically, if applied in a clinical setting, existing PRSs may exacerbate health disparities among ethnic groups. 49 The population specificity of existing PRSs as well as estimates of transethnic genetic correlations less than one reported in the literature 30,[50][51][52][53] indicate that (1) LD tagging and allele frequencies of shared causal variants vary across populations, (2) that a sizeable number of causal variants are population specific, and/or (3) that causal effect sizes vary across populations due to, for example, different gene-environment interactions. In a region with population-specific LD, a single genetic variant that is significantly associated with a trait in two populations may actually be tagging distinct population-specific causal variants (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This WEIRD gene sampling bias in GWAS is deeply problematic. Polygenic scores do not translate well across ancestry groups (Bitarello and Mathieson 2020;Guo et al 2019;Curtis 2018;Kim et al 2018;Martin et al 2017). For example, European ancestry-derived polygenic scores have only 42% of the effect size in African ancestry samples (Duncan et al 2019).…”
Section: Weird Gene Problemmentioning
confidence: 99%
“…On the other hand, several studies have shown 31 that heterogeneity in genetic architectures limits transferability of polygenic risk scores (PRS) across 32 populations 5, [41][42][43][44][45][46][47][48] ; critically, if applied in a clinical setting, existing PRS may exacerbate health disparities 33 among ethnic groups 49 . The population-specificity of existing PRS as well as estimates of transethnic 34 genetic correlations less than one reported in the literature 30,[50][51][52][53] indicate that (1) LD tagging and allele 35 frequencies of shared causal variants vary across populations, (2) that a sizeable number of causal variants 36 are population-specific, and/or (3) that causal effect sizes vary across populations due to, for example, 37 different gene-environment interactions. For example, due to population-specific LD, a single genetic 38 variant that is significantly associated with a trait in two populations may actually be tagging distinct 39 population-specific causal variants ( Figure 1).…”
Section: Introduction 18mentioning
confidence: 97%